Corporate Social Responsibility in Spanish Media Groups: Incorporation, management and analysis of information through their websites - Fernández Vázquez, Jessica (2012)
Since the nineties Corporate Social Responsibility (CRS) has become one of the major assets in enterprise management. Businesses grew aware that their activities have strong consequences in the public sphere within a continuous dialogue between both of them, reverting part of the benefits in society. Hence, CSR is a key factor in terms of public relations to improve reputation and social legitimacy, not to mention its role within the corporate identity management. In case of media involved, CSR shows two approaches: on the one hand, implementing responsible measures as for environment, stakeholders, institutions, etc. and, on the other hand, facilitating information in a rigorous, true, objective and ethical way. This paper aims at studying CSR of the major communication groups in Spain through their web pages in the context of media as public opinion generators.